2008
DOI: 10.1021/la703297q
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Self-Assembly of Quantum Dots and Block Copolymers in a Microfluidic Device

Abstract: The controlled self-assembly of polymer-stabilized quantum dots (QDs) into mesoscale aqueous spherical assemblies using microfluidics is described. In a flow-focusing configuration, self-assembly is initiated by the addition of water to a blended solution of polystyrene-coated QDs and amphiphilic polystyrene-block-poly(acrylic acid) stabilizing chains and terminated in a downstream quench step. The on-chip evolution of assemblies is monitored through fluorescence microscopy, and particle size distributions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Microfluidic techniques are widely applied in the preparation of microcapsules and monodispersed microspheres. Through this method, various shapes and morphologies polymer particles such as truncated spheres and hemispheres can be obtained [17][18][19][20][21][22][23][24][25][26][27][28]. Especially, Xia et al successfully prepared PCL microspheres for cell culture applications by using the microfluidic device [17,18] and Yang et al reported multi-functional PCL microcapsules for drug delivery by microfluidic chip method [19].…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic techniques are widely applied in the preparation of microcapsules and monodispersed microspheres. Through this method, various shapes and morphologies polymer particles such as truncated spheres and hemispheres can be obtained [17][18][19][20][21][22][23][24][25][26][27][28]. Especially, Xia et al successfully prepared PCL microspheres for cell culture applications by using the microfluidic device [17,18] and Yang et al reported multi-functional PCL microcapsules for drug delivery by microfluidic chip method [19].…”
Section: Resultsmentioning
confidence: 99%
“…This approach was instrumental in enabling the encapsulation of fluorescent and magnetic nanoparticles within the larger polymer particles. 3,22 The inclusion of cadmium sulfide quantum dots (QDs) into stabilized block copolymer particles was also demonstrated in a microfluidic device. 3,20 While a similar T-junction strategy was used, the reaction mechanism was substantially different from the spherical hydrogels just discussed.…”
Section: Organic Particles Including Polymers and Gelsmentioning
confidence: 99%
“…3,22 The inclusion of cadmium sulfide quantum dots (QDs) into stabilized block copolymer particles was also demonstrated in a microfluidic device. 3,20 While a similar T-junction strategy was used, the reaction mechanism was substantially different from the spherical hydrogels just discussed. This effort involved a selfassembly process that was monitored fluorescently such that the process could be quenched with water at an optimal point in the reaction.…”
Section: Organic Particles Including Polymers and Gelsmentioning
confidence: 99%
See 2 more Smart Citations